Pengaruh Partisipasi Anggaran dan Akuntansi Pertanggungjawaban terhadap Kinerja Manajerial - Agnes Shinta Dewi (Jurnal Riset Akuntansi, 2021)
Abstract. Budget participation and accountability accounting are two important elements in the budgeting process because with these two elements that are effective, there will be efforts to achieve the targets that have been prepared so that good performance can be achieved with the aim to know and test empirically about the influence of budget participation and accounting accountability on managerial performance in Regional Owned Enterprises (BUMD) and to know and test the dominant variables affecting managerial performance in Regional Owned Enterprises (BUMD). Regional Owned Enterprises (BUMD) is the object of this study with a sample of 30 Top managers and Middle Managers using survey techniques with questionnaires. To answer the formulation, purpose and hypothesis of research, the analysis used is multiple linear regression analysis. The results of multiple linear regression analysis concluded that the 1st hypothesis that reads "that budget participation and accountability of accountability positively affect managerial performance" tested the truth and the 2nd hypothesis that reads "that budget participation has a more dominant effect on managerial performance" tested the truth. Abstrak. Partisipasi anggaran dan akuntansi pertanggungjawaban merupakan dua unsur penting dalam proses penyusunan anggaran karena dengan adanya dua unsur tersebut yang efektif, maka akan timbul usaha untuk mencapai target yang telah disusun sehingga dapat tercapai kinerja yang baik dengan tujuan untuk mengetahui dan menguji secara empiris tentang pengaruh partisipasi anggaran dan akuntansi pertanggungjawaban terhadap kinerja manajerial di Badan Usaha Milik Daerah (BUMD) dan untuk mengetahui dan menguji variabel yang dominan mempengaruhi kinerja manajerial di Badan Usaha Milik Daerah (BUMD). Badan Usaha Milik Daerah (BUMD) merupakan obyek dari penelitian ini dengan sampel sebanyak 30 Top manajer dan Middle Manajer dengan menggunakan teknik survey dengan kuisioner. Untuk menjawab perumusan, tujuan dan hipotesis penelitian maka analisis yang digunakan adalah analisis regresi linier berganda. Hasil analisis regresi linier berganda menyimpulkan bahwa hipotesis ke-1 yang berbunyi “bahwa partisipasi anggaran dan akuntasi pertanggungjawaban berpengaruh positif terhadap kinerja manajerial” teruji kebenarannya dan hipotesis ke-2 yang berbunyi “bahwa partisipasi anggaran lebih dominan berpengaruh terhadap kinerja manajerial” teruji kebenarannya.